Exploring Muslim students' adoption of mobile banking in conventional banks - Sudarsono, Heri; Utami, Sri; Rahmi, Asri Noer; Yuniarti, Fauziah Rizki; Suciningtias, Siti Aisiyah (Asian Journal of Islamic Management (AJIM), 2024)
Purpose – This study aims to analyze the factors that influence Muslim students' intention to adopt mobile banking in conventional banks. Methodology – The research sample consisted of 170 Muslim students who used mobile banking in conventional banks. The partial least squares (PLS) method was used to evaluate the unified theory of acceptance and use of technology (UTAUT) on Muslim students' intentions to use m-banking in conventional banks. Findings – This research shows that performance expectancy, facilitating conditions, and social influence the behavioral intention of Muslim students, while effort expectancy does not influence the behavioral intention of Muslim students to adopt mobile banking at conventional banks. On the other hand, behavioral intention influences Muslim students’ behavior towards mobile banking in conventional banks.Implications – Banks should focus on highlighting user-friendly designs and providing clear, accessible information and support to overcome perceived difficulties. Emphasizing the practical benefits and efficiency of mobile banking can play a significant role in encouraging its use. Additionally, creating a supportive environment with adequate resources and leveraging positive social influences can further increase students' intentions and actual usage of mobile banking services.Originality – Research on the intention of Muslim students to adopt mobile banking at Islamic banks has been conducted by many previous researchers. Therefore, this study examines the influence of Muslim students' intention to adopt mobile banking in conventional banks, which has rarely been studied by previous researchers.